M Marketing Strategy in Moderation of Social Media & Marketplace to Increase Sales Turnover Anticipating the Impact of the Covid-19 Pandemic at Rasana Juice Surabaya - kamellia nety anggreani (IJEBD (International Journal of Entrepreneurship and Business Development))
This study aims to determine the effect of marketing strategy on sales turnover with each moderating variable, namely social media and marketplace. This research is a causal associative research with a quantitative approach, for data processing with SEM method and using SmartPLS 3.0 software. The variables analyzed in this study are product (X1), price (X2), location/distribution (X3), promotion (X4), sales volume (Y), social media (SM) and marketplace (M). The population in this study is MSMEs for beverage products with a total sample of 152 MSMEs. The data collection methods used were interviews and questionnaires with a Likert measurement scale, then the questionnaire was tested by T-test (partial) and F-test (simultaneous). The results of testing the X variable against Y with social media moderator show that all variables have a significant and positive effect except the price variable on sales volume in social media moderation (X2*SM -> Y) and promotion variables on sales volume in social media moderation (X4*SM -> Y), both results were rejected because P Value > 0.05. While the research results from testing the X variable against Y with the marketplace moderator show that all variables have a significant and positive effect except the product variable on sales volume (X1 -> Y) and the price variable on sales volume in marketplace moderation (X2*M -> Y), both results > 0.05 which means it is not significant.